Four new species of the subgenus Homoneura from Jiangxi Province, China (Diptera: Lauxaniidae: Homoneura) - Shi, Li; Gao, Xue Feng; Shen, Rong Rong (Zootaxa, 2017)
The following four species from Jiangxi Province are new to science: Homoneura (Homoneura) jiangxiensis sp. nov., H. (H.) martini sp. nov., H. (H.) pangae sp. nov. and H. (H.) stepheni sp. nov.. For each species, a diagnosis and description are provided, along with photographs of the habitus and certain characters, and figures of male genitalia. These species belong to the Homoneura (Homoneura) henanensis group (Diptera: Lauxaniidae: Homoneurinae). A key to the species of this species group is presented. This represents the first report of the genus Homoneura for Jiangxi Province. All type specimens for the new species are deposited in the Smithsonian Institution National Museum of Natural History, Washington D.C., USA (USNM).